Sculpting nanoparticle dynamics for single-bacteria-level screening and direct binding-efficiency measurement - Y. Z. Shi (Nature Portfolio, 2018)
Optical trapping is a versatile tool for biomedical applications. Here, the authors use an optofluidic lattice to achieve controllable multi-particle hopping and demonstrate single-bacteria-level screening and measurement of binding efficiency of biological binding agents through particle-enabled bacteria hopping.